Role of farmers' organizations in agricultural transformation in Africa: Overview of continental, regional, and selected national level organizations - Willi Kampmann; Oliver K. Kirui (University of Bonn, Center for Development Research (ZEF), 2021)
This study analyzes the critical role played by farmers' organizations (FOs) in transforming agriculture in Africa. Specifically, it provides an overview of the state of continental and regional FOs in Africa. It also uses three-country (Senegal, Uganda and Zambia) case studies to discuss the structure, functioning, objectives, and financing of the FOs in these selected countries. Findings show that the FOs in the three case study countries are more or less well-structured. The national-level (umbrella) FOs are linked to the local-level substructures. However, membership in these FOs is voluntary and a sizeable majority of small-scale producers is yet to be part of the organized FOs. The umbrella organizations represent just about 2.5 million, 2 million, and 550,000 (equivalent to about 30%, 10.9% and 6.4%) small-scale farmers in Senegal, Uganda, and Zambia, respectively. Evidence from the continental, regional and the three country case studies suggests that many FOs face capacity and financial constraints. Nearly all FOs are dependent on external resources. The FOs generate meagre proportion of their finances from members - just about 5% of the annual budget. Programs and incentives to rally members to contribute towards the FOs would be timely. Some viable ways of raising revenue may include strengthening of farmer-driven cooperatives, transfer of knowledge, innovation and training of members, and creating value addition through processing of agricultural produce. The evolving agricultural policies have now seen FOs assuming the roles previously played by governments, such as agricultural education, marketing of produce, and provision and distribution of farm inputs. However, many of these FOs are not equipped to do so because of limited skills, weak organizational capacity, and severe resource restraints. In the end, FOs are undermined by attempts to take on too many roles and taking on over-ambitious objectives and providing public goods. In order to move agriculture to the next level, the existing FOs require energizing, first through building the capacity of the existing leaders, increasing the membership base and their financial contribution to support the operations of the organizations, and by creating opportunities for the FOs to engage policy makers on a regular basis. Governments should also give FOs the right to sit in all decision-making bodies examining agricultural, food and rural development issues. Financial support and funding from donors should be merited and channeled to accountable organizations, and should expand its focus to include institutional development that would strengthen the FOs rather than only supporting microprojects. There is also need to improve linkages and coordination among the various projects and programs supported by donor funding.
Keywords: Q13; O13; O17; J51; 330; Farmers' organizations; smallholders; collective action; agricultural transformation; Africa